The role of Phosphodiesterase 4 in insulin- and phytocannabinoids-induced cardio-protection, and B-adrenergic cardiac damage. - Smith, Angelique (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.